IDENTITAS DAN KESETARAAN SOSIAL DALAM PEMBENTUKAN SEBUAH GEREJA DI YOGYAKARTA - Khusyairi, Johny A (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2020)
One of the important issues in the formation of Javanese Reformed-Christian (JRC) church was the usage of the Javanese language. The formation of the church did not only involve transplanting theological and ritual teachings of the Dutch Reformed Churches (GKN), but also the usage and the choice of registers of the hierarchical Javanese language for Javanese congregation. This article intends to examine the importance of Javanese in the formation of Javanese Reformed-Christian church in Yogyakarta. Archival sources, particularly of the GKN, were used to examine the importance of Javanese in the establishment of this JRC church in Yogyakarta. The author concluded that the usage of Javanese terms for “church” and “pastor”, and the choice of the highest level of the language, Krama, in church ritual was intended to preserve Javanese language and convey social equality between the Javanese and the Dutch.